2016
DOI: 10.1016/j.ejcdt.2015.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcome of ICU admitted MERS corona virus infected patients

Abstract: Middle East Respiratory Syndrome (MERS) is a novel respiratory illness firstly reported in Saudi Arabia in 2012. It is caused by a new corona virus, called MERS corona virus (MERS-CoV). Most people who have MERS-CoV infection developed severe acute respiratory illness.Aim of the work: This work is done to determine the clinical characteristics and the outcome of intensive care unit (ICU) admitted patients with confirmed MERS-CoV infection.Patients and methods: This study included 32 laboratory confirmed MERS c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 28 publications
3
36
1
Order By: Relevance
“…Most of the studies (n = 35) [2,4,12,13,[16][17][18][19][20][21][22][23][24][25]27,[30][31][32][33][35][36][37][38][40][41][42][44][45][46][47][48][49][50][51][52] were observational and retrospective. We extracted data from eleven (n = 11) English abstracts provided for Chinese articles [17,26,30,32,34,35,37,38,42,44,48] and for one (n = 1) commentary [19].…”
Section: Descriptive Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the studies (n = 35) [2,4,12,13,[16][17][18][19][20][21][22][23][24][25]27,[30][31][32][33][35][36][37][38][40][41][42][44][45][46][47][48][49][50][51][52] were observational and retrospective. We extracted data from eleven (n = 11) English abstracts provided for Chinese articles [17,26,30,32,34,35,37,38,42,44,48] and for one (n = 1) commentary [19].…”
Section: Descriptive Datamentioning
confidence: 99%
“…There were 11 (n = 11) [2,4,12,[16][17][18][19][20][21][22][23] studies focusing on SARS CoV-2 and 23 (n = 23) [13, which reported data on patients infected with SARS CoV-1. MERS had the last amount of data (n = 9) [8,[46][47][48][49][50][51][52][53]. Overall, we analyzed clinical characteristics of 4591 subjects, most with SARS CoV-2 (n = 2541), followed by SARS CoV-1 (n = 1894) and MERS (n = 156).…”
Section: Descriptive Datamentioning
confidence: 99%
“…The challenge of COVID-19 is very high globally due to a lack of proven treatment and the complexity of its transmission 13,[21][22][23][24][25][26][27] . However, it will be more catastrophic for low and middleincome countries because of very poor health care system, high illiteracy and low awareness of the disease and its prevention, lack of skilled health personnel, scarce Intensive Care Unit, a limited number of mechanical ventilators and prevalence of co-morbidities/infection along with malnutrition.…”
Section: Introductionmentioning
confidence: 99%
“…The outcomes of patients with coronavirus infection are very variable. Studies revealed that in hospital mortality of patients with COVID-19 was very high which varied from 1% 52% of hospitalized patients 21,[23][24][25]32,[34][35][36][37] . Studies also showed that rate of ICU admission among coronavirus infected patients were higher which ranged from 3% to 100% of confirmed cases 11,21,[23][24][25]27,28,32,36,[38][39][40] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation